Electro-Conductive Composite Gold-Polyethersulfone-Ultrafiltration-Membrane: Characterization of Membrane and Natural Organic Matter (NOM) Filtration Performance at Different In-Situ Applied Surface Potentials - Tomi Mantel; Paul Benne; Stanislav Parsin; Mathias Ernst (Membranes, 2018)
Next to the pore size distribution, surface charge is considered to be one main factor in the separation performance of ultrafiltration (UF) membranes. By applying an external surface potential onto an electro-conductive UF membrane, electrostatic induced rejection was investigated. This study introduces in a first part a relatively simple but yet not reported technology of membrane modification with direct current sputter deposition of ultrathin (15 nm) highly conductive gold layers. In a second part, characterization of the gold-coated UF flat sheet membrane with a molecular weight cut-off (MWCO) of 150 kDa is presented. Membrane parameters as contact angle (hydrophobicity), pure water permeability, MWCO, scanning electron microscopy imaging, zeta potential, surface conductivity and cyclic voltammetry of the virgin and the modified membrane are compared. Due to the coating, a high surface conductivity of 107 S m−1 was realized. Permeability of the modified membrane decreased by 40% but MWCO and contact angle remained almost unchanged. In a third part, cross-flow filtration experiments with negative charged Suwannee River Natural Organic Matter (SRNOM) are conducted at different cathodic and anodic applied potentials, different pH values (pH 4, 7, 10) and ionic strengths (0, 1, 10 mmol L−1). SRNOM rejection of not externally charged membrane was 28% in cross-flow and 5% in dead-end mode. Externally negative charged membrane (−1.5 V vs. Ag/AgCl) reached rejection of 64% which was close to the performance of commercial UF membrane with MWCO of 5 kDa. High ionic strengths or low pH of feed reduced the effect of electrostatic rejection.